Digital Transformation in Lesson Planning: Automating Semester Learning Plans to Improve Pedagogical Effectiveness - Hasanah, Uswatun; Sibilana, Annas Ribab (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
Digital transformation in education has become crucial to improving effectiveness in academic processes. This study aims to develop the RTFAC application to enhance the efficiency of the Semester Learning Plan (Rencana Pembelajaran Semester) formulation. The research employs the research and development method with the Borg & Gall model. The subjects involved in this study include experts, PGMI and PAI lecturers, researchers, and the university's quality assurance institution. The study resulted in a product in the form of an RPS formulation application called RTFAC. Product testing results on aspects such as feature compatibility with RPS formulation needs, application functionality quality, user interface, application performance efficiency, curriculum alignment, and data reliability and security, as assessed by expert validators, are deemed highly feasible. Based on the effectiveness test using a one-sample t-test, it was found that the RTFAC application significantly improves the efficiency of RPS formulation. Therefore, the RTfac application at UIN Sayyid Ali Rahmatullah Tulungagung is expected to reduce lecturers' workload in formulating semester learning plans (RPS), which may contribute to enhanced pedagogical effectiveness.